In vitro and in vivo transcription from a computer predicted promoter - Sázelová, P; Felsberg, J; Pivec, L (Gene, 1997)
A fragment (172 bp) of B. subtilis phage phi29 DNA, which does not contain a functional promoter for phage transcription, has been shown to direct transcription in the promoter-probe plasmid pPV33. The promoter candidate found in this fragment by the computer method of acceptability is compared with cryptic promoters selected by this computer method. It is characterized in vitro by electron microscopic visualization of RNA polymerase binding and 'run off' transcription, and in vivo by high resolution S1 mapping.
Keywords: Bacillus subtilis; Base Sequence; Bacillus Phages; počítačová simulace; mapování chromozomů; Single-Strand Specific DNA and RNA Endonucleases; Chromosome Mapping; DNA, Viral; Transcription, Genetic; Molecular Sequence Data; Tetracycline Resistance; Computer Simulation; genetická transkripce; molekulární sekvence - údaje; rezistence na tetracyklin; plazmidy; Cloning, Molecular; DNA-Directed RNA Polymerases; sekvence nukleotidů; DNA řízené RNA-polymerasy; exprese genu; klonování DNA; fágy bacilů; promotorové oblasti (genetika); Plasmids; Promoter Regions, Genetic; endonukleasy specifické pro jednořetězcové nukleové kyseliny; Gene Expression; DNA virů